Strategic consensus mapping: A new method for testing and visualizing strategic consensus within and between teams. (2nd August 2013) - Tarakci, Murat; Ates, Nufer Yasin; Porck, Jeanine P.; van Knippenberg, Daan; Groenen, Patrick J.F.; de Haas, Marco
<x xml:space="preserve">Abstract</x> Research on strategic consensus focuses primarily on the extent of agreement among team members regarding organizational strategy. It does not include elements such as the content of the agreement, between‐group consensus, or the significance of differences in consensus (e.g., for evaluating the effectiveness of strategic interventions). We propose a new analytical approach, Strategic Consensus Mapping, that provides a comprehensive analysis of strategic consensus within and between groups and that includes intuitive and easy‐to‐understand visualizations. This approach offers researchers the necessary tools for integrative theory building in strategic consensus, as well as in the broader managerial and organizational cognition domain. Using a case example, we illustrate the proposed methods for a multidimensional, multilevel, and longitudinal analysis of strategic consensus. Copyright © 2013 John Wiley & Sons, Ltd.